Geophysical study of a salt body for energy storage (Geo-Eco-Marina, 2017)
In the context of global and national efforts to mitigate climate change, renewable energies from intermittent sources are starting to have considerable shares in the global and national energy mix. In order to maintain security and stability of energy networks, there is an increasing need for energy storage. Geological (underground) energy storage could be a solution for storing large amounts of energy and, at present, there are several technologies, at different levels of maturity. We decided to start the evaluation of geological energy storage possibilities in Romania with the evaluation of salt caverns created through dissolution during salt exploitation through boreholes. After selection, several salt caverns were, geophysically, investigated in an area of salt exploitation from Romania. The results of the gravity and electric survey indicated that the investigated caverns have stability problems and that there is a channel through which the brine is circulating between caverns.
Keywords: Gravity survey; rezistivity survey; modelling; salt cavern